2010
DOI: 10.1051/0004-6361/200912965
|View full text |Cite
|
Sign up to set email alerts
|

Chemical abundance analysis of the open clusters Cr 110, NGC 2099 (M 37), NGC 2420, NGC 7789, and M 67 (NGC 2682)

Abstract: Context. The present number of Galactic Open Clusters that have high resolution abundance determinations, not only of [Fe/H], but also of other key elements, is largely insufficient to enable a clear modeling of the Galactic Disk chemical evolution. Aims. To increase the number of Galactic Open Clusters with high quality measurements. Methods. We obtained high resolution (R∼30 000), high quality (S/N∼50-100 per pixel), echelle spectra with the fiber spectrograph FOCES, at Calar Alto, Spain, for three red clump… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

52
206
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 194 publications
(265 citation statements)
references
References 197 publications
52
206
6
Order By: Relevance
“…The gradients defined by OCs have been the subject of previous studies. The current picture suggests a gradient for [Fe/H] of about −0.06 dex kpc −1 (Friel et al 2002;Pancino et al 2010) to −0.20 dex kpc −1 (Frinchaboy et al 2013) in the radial range 5 to 10 kpc with a nearly flat trend (−0.02 dex kpc −1 ) over the entire radial extent of the disc at Rgc >12 kpc, with a break occurring around 11 kpc Pancino et al 2010;Yong et al 2012;Frinchaboy et al 2013). We show in figure 4, the run of [Fe/H] versus Rgc (top panel) and [α/Fe] versus Rgc (bottom panel) for the present homogeneous sample of 79 OCs (a total of 28 OCs from our study and 51 OCs from the literature).…”
Section: Radial Abundance Distribution Of Ocs and The Field Starsmentioning
confidence: 80%
See 2 more Smart Citations
“…The gradients defined by OCs have been the subject of previous studies. The current picture suggests a gradient for [Fe/H] of about −0.06 dex kpc −1 (Friel et al 2002;Pancino et al 2010) to −0.20 dex kpc −1 (Frinchaboy et al 2013) in the radial range 5 to 10 kpc with a nearly flat trend (−0.02 dex kpc −1 ) over the entire radial extent of the disc at Rgc >12 kpc, with a break occurring around 11 kpc Pancino et al 2010;Yong et al 2012;Frinchaboy et al 2013). We show in figure 4, the run of [Fe/H] versus Rgc (top panel) and [α/Fe] versus Rgc (bottom panel) for the present homogeneous sample of 79 OCs (a total of 28 OCs from our study and 51 OCs from the literature).…”
Section: Radial Abundance Distribution Of Ocs and The Field Starsmentioning
confidence: 80%
“…Abundance gradients in the Milky Way can be measured using a wide variety of tracers including the young population of H ii regions, OB stars, and Cepheid variables, and planetary nebulae of different ages, cool unevolved stars and red giants in the field (see for example, Magrini et al 2010;Cheng et al 2012;Hayden et al 2014) and in open clusters (OCs; Friel et al 2002Friel et al , 2010Magrini et al 2010;Pancino et al 2010;Yong et al 2012;Frinchaboy et al 2013). The cooler main sequence stars or red giants which are members of OCs provide not only abundance estimates for elements sampling all the major processes of stellar nucleosynthesis -but a collection of stars whose age, distance, kinematics and metallicity can be measured with greater certainty than for field stars.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally the spectra were summed -after correcting for radial velocity shifts -to produce one single spectrum for each of the six observed stars. Radial velocities were obtained with DAOSPEC 2 (Stetson & Pancino 2008) and the procedure described by Pancino et al (2010). In short, the laboratory wavelength of selected absorption lines (Sect.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…These studies have confirmed the steep slope in the gradient for 7 kpc < R GC < 11 kpc and have shown that the distribution becomes flatter for Galactocentric distances (R GC ) above 11−12 kpc (cf. Magrini et al 2009, hereafter M09, but see Pancino et al 2010 for a different view).…”
Section: Introductionmentioning
confidence: 99%